Poly (ADP-Ribose) Polymerase 1 Mediated Arginase II Activation Is Responsible for Oxidized LDL-Induced Endothelial Dysfunction - Qi Wang; Tong Zhao; Wei Zhang; Wenbin Yu; Bin Liu; Zhaoyang Wang; Wen Qiao; Qinghua Lu; Aihua Wang; Mingxiang Zhang; Mingxiang Zhang (Frontiers Media S.A., 2018)
It is well known that arginase II leads to decreased synthesis of nitric oxide (NO) by competing with endothelial nitric oxide synthase (eNOS) for their same substrate L-arginine. However, the regulatory mechanisms of arginase II production remain unclear. In this study, we hypothesized that poly- (ADP-ribose) transferase/polymerase-1 (PARP-1) may be a critical factor responsible for ox-LDL (oxidized Low Density Lipoprotein)-enhanced arginase II activity. We used serial deletions within plasmid constructs and found that a core promoter region of arginase II was located at the element of -774 to -738 bp and PARP-1 was identified specifically binding to this region. Inhibition of PARP-1 markedly reduced the endogenous arginase II expression and enhanced eNOS and NO production. Similarly, ox-LDL-induced increase in arginase II production and eNOS and NO reduction was substantially abolished by PARP-1 inhibition both in vitro and in vivo. Significant decrease in arginase II expression and increase in eNOS expression and NO levels, as well as improved endothelial function were observed in PARP-1-/- mice. The underlying mechanisms of ox-LDL-induced changes of PARP-1 expression involved migration of phosphorylated ERK2 into nuclei and direct interaction with PARP-1 which dramatically enhanced PARP-1 production, followed by histone acetylation to activate arginase II transcription process. Our studies demonstrated for the first time that PARP-1 regulates basal transcription process and ox-LDL-induced up-regulation of arginase II. These results demonstrated that PARP-1 offers a promising therapeutic target for endothelial dysfunction and atherosclerosis.